Rapid detection and differentiation of mycobacterial species using a multiplex PCR system - Lima,Andrea Santos (2013)
Introduction The early diagnosis of mycobacterial infections is a critical step for initiating treatment and curing the patient. Molecular analytical methods have led to considerable improvements in the speed and accuracy of mycobacteria detection. Methods The purpose of this study was to evaluate a multiplex polymerase chain reaction system using mycobacterial strains as an auxiliary tool in the differential diagnosis of tuberculosis and diseases caused by nontuberculous mycobacteria (NTM) Results Forty mycobacterial strains isolated from pulmonary and extrapulmonary origin specimens from 37 patients diagnosed with tuberculosis were processed. Using phenotypic and biochemical characteristics of the 40 mycobacteria isolated in LJ medium, 57.5% (n=23) were characterized as the Mycobacterium tuberculosis complex (MTBC) and 20% (n=8) as nontuberculous mycobacteria (NTM), with 22.5% (n=9) of the results being inconclusive. When the results of the phenotypic and biochemical tests in 30 strains of mycobacteria were compared with the results of the multiplex PCR, there was 100% concordance in the identification of the MTBC and NTM species, respectively. A total of 32.5% (n=13) of the samples in multiplex PCR exhibited a molecular pattern consistent with NTM, thus disagreeing with the final diagnosis from the attending physician. Conclusions Multiplex PCR can be used as a differential method for determining TB infections caused by NTM a valuable tool in reducing the time necessary to make clinical diagnoses and begin treatment. It is also useful for identifying species that were previously not identifiable using conventional biochemical and phenotypic techniques.